Simultaneous EEG-fMRI in Patients with Unverricht-Lundborg Disease: Event-Related Desynchronization/Synchronization and Hemodynamic Response Analysis. (6th January 2010) - Visani, Elisa; Minati, Ludovico; Canafoglia, Laura; Gilioli, Isabella; Salvatoni, Lucia; Varotto, Giulia; Fazio, Patrik; Aquino, Domenico; Bruzzone, Maria Grazia; Franceschetti, Silvana; Panzica, Ferruccio
Abstract : We performed simultaneous acquisition of EEG-fMRI in seven patients with Unverricht-Lundborg disease (ULD) and in six healthy controls using self-paced finger extension as a motor task. The event-related desynchronization/synchronization (ERD/ERS) analysis showed a greater and more diffuse alpha desynchronization in central regions and a strongly reduced post-movement beta-ERS in patients compared with controls, suggesting a significant dysfunction of the mechanisms regulating active movement and movement end. The event-related hemodynamic response obtained from fMRI showed delayed BOLD peak latency in the contralateral primary motor area suggesting a less efficient activity of the neuronal populations driving fine movements, which are specifically impaired in ULD.